European Union Membership as a Shield? Corruption and Foreign Investment in Romania - Alexandra Horobeț; Mihai Cazacu; Oana Cristina Popovici; Cristiana Coman; Ioana Luciana Grozea (Romanian Journal of European Affairs)
This study examines the intricate relationship between corruption and Foreign Direct Investment (FDI) in Romania, an emerging market and a European Union Member State that is undergoing significant institutional transformation. Through a comprehensive questionnaire distributed to Romanian businesses, the research investigates how corruption perceptions impact investment environments and strategic decision-making. The research reveals a nuanced business landscape, where approximately 70% of respondents express moderate satisfaction with the current investment climate, while acknowledging persistent challenges coming from institutional inefficiencies and corruption. Findings indicate that although explicit bribery is not widespread, corrupt practices permeate transactional processes across public and private sectors, potentially influencing the investment dynamics. An interesting finding is the almost overwhelming acknowledgement of Romania’s membership in the European Union as a comparative advantage for doing business in the country. The paper contributes to the limited literature on country-specific corruption perceptions by providing empirical insights into Romania’s unique context, considering its European Union membership and postcommunist transition. Key recommendations include the development of governmental infrastructure, enhanced regulatory practices, and targeted anti-corruption strategies. Acknowledging its methodological limitations, particularly the low response rate, the research calls for further investigations that extend the analysis at the level of Central, Eastern and Southern Europe and explore how anti-corruption policies might influence FDI presence.